Understanding Science-Contextualized Numeracy: A Study of Grade XI Students in the Bandung Area - Puti Siswandari; Miarti Khikmatun Nais; Fitri Rahmawati (Postgraduate, University of Mataram, 2025)
Numeracy skills in the context of science are crucial in helping students understand and interpret scientific phenomena quantitatively. However, there has been no comprehensive review of students' numeracy skills in the context of science in secondary schools, particularly in the Bandung area. This study aims to describe the level of numeracy skills in the context of science and identify areas of student weakness. The method used is descriptive quantitative, involving 121 11th-grade students from several schools. Students who had taken science subjects (physics, chemistry, and biology) in 10th grade were assessed on numeracy skills covering five numeracy domains: arithmetic, algebra, data processing, graphing, and geometry. The data were analyzed descriptively using mean values, standard deviations, and minimum and maximum score ranges. These findings indicate that students' numeracy skills are generally in the moderate to low category, with a wide distribution of scores. Data processing is the domain with the highest success rate, while arithmetic received the lowest average score of the five numeracy domains. Strengthening in arithmetic operations is also needed to calculate decimals, ratios, fractions, and percentages. These results indicate the need to integrate numeracy content into science learning to strengthen students' numeracy skills.